A novel current steering method for targeted spinal cord stimulation - Mishra, Lakshmi Narayan; Kulkarni, Gaurav; Gadgil, Mandar (Frontiers in Pain Research, 2023)
Spinal Cord Stimulation (SCS) with leads embedded in the epidural space has become a recognized and effective clinical therapy for chronic pain relief. Leads with multiple electrodes placed close to the spinal cord allow targeted stimulation. This paper presents a novel current steering method to achieve targeted spinal cord stimulation by determining the optimal current sourced through a set of electrodes to maximize current density in a specified region of the spinal cord. The method provides a flexibility for personalized pain relief therapy, while minimizing stimulation in unwanted regions. The paper proposes a new optimization problem to achieve current steering. The optimization problem uses a solution of the Poisson equation evaluated using Finite Element Analysis (FEA) over a geometric model of the spinal cord and the embedded leads. The solution to the optimization problem determines the optimal current sourced through a set of electrodes to achieve a targeted stimulation.